English as Foreign Language Student Teachers’ Perceptions of the Use of Moodle in a Foundations of Education Course (Malaysian Journal of Learning and Instruction, 2008)
In order to design an effective e-learning environment, the present study investigated English as Foreign Language (EFL) students’ perceptions of the use of Moodle as a course management system in a Foundations of Education (FOE) course at the College of Education. The study also aimed at exploring statistically significant differences between student teachers’ perceptions that can be attributed to gender, residence, year in the program, computer skills, and GPA variables. Data were collected from a sample of 60 students using a questionnaire. Findings showed that using Moodle increases students’ participation in learning, exchanging ideas and knowledge (μ = 4.37). Over half the total number of students preferred to use chat rooms and forums in computer labs to formal lecture rooms. Findings also showed that there are statistically significant differences between student responses related to year in the program in favor of students in their third and fourth year. With regard to obstacles facing students, the findings showed that most of these obstacles revolve around technical issues and frequent computer errors. Based on these findings, several recommendations were made.